2019
DOI: 10.1136/bmjopen-2019-034502
|View full text |Cite
|
Sign up to set email alerts
|

Age and nationality in relation to injuries at sea among officers and non-officers: a study based on contacts from ships to Telemedical Assistance Service in Denmark

Abstract: ObjectivesCharacterisation of worker injuries on board merchant ships is modest. Using telemedical service contacts in Denmark, we describe the worker injuries patterns and factors related to injury incidence.MethodsThe data for this study were based on contacts (n=1401) from ships to Telemedical Assistance Service (TMAS) in Denmark in 2004–2014, which were supplemented with data on the annual estimation of all seafarers from the Danish Maritime Authority (n=73 336). The final data included information on broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Nearly 30% of injuries occurred in the wrist and hand, followed by the knee and lower leg (21%). Our results agree with the study conducted in the Danish-flagged merchant fleet, 18 which reported 36% and 18% of upper and lower limb injuries, respectively. Moreover, this study revealed that non-officers were more likely than officers to be injured (IRR=1.75).…”
Section: Discussionsupporting
confidence: 92%
“…Nearly 30% of injuries occurred in the wrist and hand, followed by the knee and lower leg (21%). Our results agree with the study conducted in the Danish-flagged merchant fleet, 18 which reported 36% and 18% of upper and lower limb injuries, respectively. Moreover, this study revealed that non-officers were more likely than officers to be injured (IRR=1.75).…”
Section: Discussionsupporting
confidence: 92%
“…Offshore operating locations are challenging for delivering emergency medical care to personnel due to inadequate coverage of communication networks, bad weather conditions, absence of health professionals, or trained paramedics on board. However, regardless of these limitations, for the last 50 years, telemedicine by use of various means of communication such as telephone [22, 23, 26, 28, 30, 32-34, 37, 39-43, 46, 47], radio [22,23,26,27,34,36,39,40,44,45,47,48], videoconference [24,25,29,47], email [26, 28, 30-35, 37-42, 46-48], and telefax [22,23,28,34] has been offered different emergency medical services at sea successfully. As a result, telemedicine in the maritime industry has made it possible to reduce number of unnecessary evacuations (nearly by 20% per year), reduce treatment delay, improve the perception of safety, and increase patient satisfaction [29,32,49,50].…”
Section: Discussionmentioning
confidence: 99%
“…For example, our recent study, based on data on contacts from ships to the RMD, found a higher risk for most types of injuries on board in younger and older ages as compared with those aged 30-49 years [16].…”
Section: Comparisons With Other Studiesmentioning
confidence: 95%